2005
DOI: 10.1128/jb.187.9.3267-3272.2005
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the Receiver and Phosphotransfer Domains of ArcB for Efficient Dephosphorylation of Phosphorylated ArcA In Vivo

Abstract: The Arc two-component system, comprising the ArcB sensor kinase and the ArcA response regulator, modulates the expression of numerous genes in response to the respiratory conditions of growth. Under anoxic growth conditions, ArcB autophosphorylates and transphosphorylates ArcA, which in turn represses or activates its target operons. Under aerobic growth conditions, phosphorylated ArcA (ArcA-P) dephosphorylates and its transcriptional regulation is released. The dephosphorylation of ArcA-P has been shown to oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 30 publications
1
43
0
5
Order By: Relevance
“…This network probably contains additional components, as RssB can also be activated by acetyl phosphate in a physiologically relevant way (Bouché et al 1998; see also below). Phosphorylation of ArcA by acetyl phosphate can also occur, and in the absence of ArcB, is likely to become relevant for ArcA activity (Pena-Sandoval et al 2005). Both branches of this network cooperate to maintain Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This network probably contains additional components, as RssB can also be activated by acetyl phosphate in a physiologically relevant way (Bouché et al 1998; see also below). Phosphorylation of ArcA by acetyl phosphate can also occur, and in the absence of ArcB, is likely to become relevant for ArcA activity (Pena-Sandoval et al 2005). Both branches of this network cooperate to maintain Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…ArcA and RssB are phosphorylated and cooperate to keep S levels low by repressing rpoS transcription and stimulating S proteolysis, respectively. Accessory components are acetyl phosphate, which contributes to RssB and perhaps also to ArcA phosphorylation (Bouché et al 1998;Pena-Sandoval et al 2005), as well as cAMP-CRP, which in log-phase cells has an indirect inhibitory effect on rpoS transcription (Lange and Hengge-Aronis 1994;F. Mika and R. Hengge, in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicates that the cytokinin receptor AHK4 determines phosphate flux through the system by regulating a bidirectional phosphorelay to and from the AHPs (Mahonen et al, 2006b). A bidirectional phosphorelay is also used by the bacterial Arc two-component system to mediate signal decay: the phosphoryl group from the ArcB response regulator is transferred back to the receiver domain of the ArcA tripartite His kinase via its His transmitter domain (Georgellis et al, 1998;Pena-Sandoval et al, 2005). It is possible that type-A ARR function may act by a similar mechanism of reverse phosphotransfer from type-B ARRs to type-A ARRs via AHPs, because phosphotransfer from AHPs to both type-A and type-B ARRs has been demonstrated in vitro Imamura et al, 2001Imamura et al, , 2003 and, in the presence of cytokinins, type-A ARRs, type-B ARRs, and AHPs mostly localize to the same subcellular compartments (Hwang and Sheen, 2001;Imamura et al, 2001Imamura et al, , 2003Kiba et al, 2003).…”
Section: Type-a Arr Protein Phosphorylation and Stabilitymentioning
confidence: 99%
“…Under aerobic growth conditions, the quinone electron carriers inhibit the kinase activity of ArcB (8) through the oxidation of two redox-active cysteine residues that participate in intermolecular disulfide bond formation (24). Under such conditions, ArcB catalyzes the dephosphorylation of ArcA-P via an Asp 54 3 His 717 3 Asp 576 3 P i reverse phosphorelay (6,28). It has been previously reported that histidine kinases act as homodimers (4,33,35,36) and that they autophosphorylate by an intermolecular reaction (32).…”
mentioning
confidence: 99%